ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH DI KSUS “KARYA BAROKAH” - Agni Andhita Rachma; Muhammad Tho’in; Iin Emy Prastiwi (Jurnal Ilmiah Ekonomi Islam, 2026)
The purpose of this study was to determine the effect of tangible factors on customer satisfaction at KSUS Karya Barokah. To determine the effect of responsiveness factors on customer satisfaction at KSUS Karya Barokah. To determine the effect of reliability factors on customer satisfaction at KSUS Karya Barokah. To determine the effect of assurance factors on customer satisfaction at KSUS Karya Barokah. This study was conducted at KSUS Karya Barokah Purwantoro, Wonogiri City. The sample in this study was 100 respondents. Data collection techniques using questionnaires. Data analysis techniques using multiple linear regression analysis. The results of the study showed that tangible, responsiveness, reliability, assurance, and empathy had a simultaneous and significant effect on customer satisfaction at KSU Karya Barokah. Tangible had a positive and significant effect on customer satisfaction at KSU Karya Barokah. Responsiveness had a positive and significant effect on customer satisfaction at KSU Karya Barokah. Reliability had a positive and significant effect on customer satisfaction at KSU Karya Barokah. Assurance had a positive and significant effect on customer satisfaction at KSU Karya Barokah. Empathy had a positive and significant effect on customer satisfaction at KSU Karya Barokah.